Central Asian Nomads in the Spread of Buddhism in Russia - Baatr U. Kitinov (RUDN Journal of World History)
The history of Buddhism in Middle Asia and its subsequent transition to Russia is rich in every dimension: in peoples and lands, events, processes, which played an important role in the history of religion, etc. This long journey lasted for centuries, when Buddhism managed to enrich local cultures with its ideas, while demonstrating the ability to transform itself, giving new features to its spiritual achievements and at the same time incorporating them into the cultures of nations that accepted the teachings of Buddha later. India, where Buddhism first originated, and Russia are separated by vast distances, and many peoples of Central Asia made their contributions to the development of local forms of Buddha’s teachings. In particular, those were such peoples as Afghans, Parthians, Kushans, Uyghurs, Mongols, Oirats, etc. Buddhism first penetrated into Middle Asia during the era of the Macedonian campaigns and took hold due to its tolerance to and complementarity with the local cults and beliefs. There are two stages in the history of Buddhism in Central Asia: first in its western part (where it would persist until the 7th-9th centuries) mainly among the Turks, then in the eastern part (from no later than the 7th century onwards), when Buddhism would manifest itself among the Zhuzhans (a stele found in the Bulgan aimag of Mongolia). The resettlement of Western Mongolian Oirats to southern Siberia in the second half of the 16th century marks the arrival of Tibetan Buddhism in Russia; however, one can also identify traces of earlier influence of Uyghur Buddhism on these nomads. In addition, the research looks at the way Kalmyks and Indians interacted in the sphere of Buddhism, and at how Buddhism was consolidating its position among the Buryats, Tuvinians and the peoples of Altai. The author mainly focuses on the territory of present-day Russia, although the study of Buddhism history in the territory of the former Russian Empire or the USSR definitely shows a more impressive heritage. The study highlights principal geographical areas and directions of Buddhism advance towards Russia, and indicates the role of certain individuals and peoples.